Art as Alterity in Education. Issue 3 (June 2014) - Zhao, Guoping
Abstract In education, art has often been perceived as entertainment and decoration and is the first subject to go when there are budget cuts or test‐score pressures. Drawing on Emmanuel Lévinas's idea of the primacy of radical alterity that breaks the totality of our being, enables self‐transformation and ethics, and ensures community as a totality of singularities, and on Maurice Blanchot's expansion of radical alterity to art, Guoping Zhao argues that the role of art in education must be reconsidered and greatly expanded. Art as alterity takes students beyond where they are and what they have, and teaches them to appreciate and respect difference and diversity. If art as alterity is so essential to human subjectivity and society, and if education is conceived as a process of human growth and formation, art as alterity is essential to education and needs to be more seriously engaged and more fully integrated into the whole educational process instead of being isolated in arts education. Zhao concludes the essay by pondering the pedagogical implications of such a reconsideration of art as alterity in education.